2008
DOI: 10.1016/s1976-1317(08)60037-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Profiles of Korean-Americans, Non-Hispanic Whites and Blacks With and Without Hypertension in the United States

Abstract: The findings suggest that protein may be needed to replace excessive carbohydrate intake in Korean-Americans and to replace fat intake in Whites and Blacks. Health professionals need to emphasize the importance of increasing calcium and potassium intake and decreasing sodium intake in their nutrition education for these ethnic groups to help prevent and control hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Our data support a previous study, which suggests that there are no differences in sodium intake between Korean Americans and non-Hispanic whites or non-Hispanic blacks. 25 However, other studies indicate children in some Asian subgroups may consume more sodium, on average, than non-Hispanic whites and that the diets of Asian Americans may be composed of both traditional Asian foods and components of a Western diet. 26,27 Recent data also suggest Asian subgroups may differ in their hypertension risks.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support a previous study, which suggests that there are no differences in sodium intake between Korean Americans and non-Hispanic whites or non-Hispanic blacks. 25 However, other studies indicate children in some Asian subgroups may consume more sodium, on average, than non-Hispanic whites and that the diets of Asian Americans may be composed of both traditional Asian foods and components of a Western diet. 26,27 Recent data also suggest Asian subgroups may differ in their hypertension risks.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies were found to be limited in the literature. Three other articles have been published from our large data set, focusing on different aspects of patients with hypertension in Kim et al. (2005, 2007, 2008).…”
Section: The Studymentioning
confidence: 99%